PARTISIPASI POLITIK PENYANDANG DISABILITAS MENTAL PADA PEMILU 2014 DAN PEMILU 2019 - Yasmine Nauly (2023)
This thesis aims to examine specifically how the participation of people with mental disabilities in the 2019 election. Voters from people with mental disabilities have increased from 500% of the total number of elections in the 2014 election to the 2019 election, so researchers are trying to see the cause of the phenomenon of the increase in percentage significance in the number of voters. This study uses the concept of Citizenship by looking at it based on political participation in the form of the use of political rights, namely the right to vote because the problems explored are a new phenomenon. The method used is a qualitative approach with data collection techniques in the form of interviews with research subjects, namely persons with mental disabilities consisting of activists and also from persons with mental disabilities themselves and other persons with general disabilities, as well as from the KPU RI as executor of the general election, Healthy Mental Association (PJS) as a representative of people with mental disabilities and journalist Tirto.Id. The results of this study found that the use of the right to vote for persons with mental disabilities in the 2019 general election was not the main cause or reason for the increase in the high political participation of the people, which reached 81%. The percentage increase of 500% was not the cause of high political participation, but identity politics, Constitutional Court regulations Number 135/PUU-XIII/2015, and KPU RI Decree Number 1401/PL. 02.1-SD/01/KPU/CI/2018 made the number of persons with mental disabilities registered and exercising their right to vote in the 2019 election so that there was an increase in voters between the 2014 election and the 2019 election.